Analyzing performance super-capacitor and battery in low voltage electrical distribution systems electronic resource - Ahmed Amin, Maarof Al-Janad (2014)
This dissertation presents a comparative study of two types of energy storage comprising of a super capacitor and a battery for reduction of harmonics in the inverter output. This dissertation deals with design and simulation of a three phase inverter in MATLAB/ SIMULINK environment and Graphical User Interface (GUI). The proposed system is designed using MA TLAB/SJMULINK and it consists of a super capacitor and a battery as energy storage, Voltage Source Inve1ter (VSI) and filtering scheme. The controller is based on the synchronous d-q reference frame technique specifically applied to the three phase inverter and the Phase Lock Loop (PLL) is used for synchronization between grid connected voltage and inverter voltage. The design of low pass filter at the inverter output meant to remove the high frequency ripple is also discussed. The various performances of simulation results between the super capacitor and the battery have been investigated. The Total Harmonic Distortion (THO) of the inverter output voltage is measured for the two types of energy storages applied to the inverter input. All simulation results are controlled and interfaced by using GUI. It can be observed that the THO voltage for the super capacitor is considerably lower than that of the battery.